Variability and Difficulty in Translating Interjections (based on Russian and Kabardino-Circassian Languages) - A. A. Afaunova (Tokova) (Научный диалог, 2020)
The results of a comparative analysis of translated Russian texts of literary works with their original in the Kabardino-Circassian language are presented. Special attention is paid to the problems of translating interjections from one language into another. It is proved that the translator must have knowledge of the grammatical structure of the translated material and take into account the slightest semantic shades of words. Our observations revealed the features of borrowing interjections from the Russian language into Kabardian speech, which, assimilating, become part of linguistic culture. The novelty of the work is seen in the fact that in Kabardino-Circassian linguistics there are no scientific works devoted to the problems of translation of interjections. All available publications concerning this subject are literary. The relevance of the work is due to the need to improve the system of approaches to the translation of interjection units, since they are not taken into account by translators in due measure. A phonetic-morphological classification of methods for translating interjections is proposed in the article. It is proved that for an adequate and accessible translation of interjections as such, knowledge from the fields of phonetics, morphology, and semantics is most important.